1948
DOI: 10.1103/physrev.74.1818
|View full text |Cite
|
Sign up to set email alerts
|

The Heavy Component of Primary Cosmic Rays

Abstract: Further evidence is presented for the existence of heavy nuclei as components of the primary cosmic radiation. Preliminary results are given for the distribution in atomic numbers of these components. Lower limits of the energies of the particles on entrance into the atmosphere are calculated. These are, in general, above the cut-off imposed by the earth's magnetic field. The mean free path for nuclear collisions is of the order of 14 cm of photographic emulsion. This is longer than that expected from the geom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
4

Year Published

1952
1952
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(15 citation statements)
references
References 7 publications
0
11
0
4
Order By: Relevance
“…Evidence for nuclei as heavy as iron came from balloon flights of cloud chambers and photographic emulsions [Freier et al, 1948a[Freier et al, , 1948b. Evidence of electrons in cosmic rays came from balloon flights of a cloud chamber [Earl, 1961] and a scintillator telescope [Meyer and Vogt, 1961].…”
Section: What Are Cosmic Rays? Geomagnetism Helps Find the Answermentioning
confidence: 99%
“…Evidence for nuclei as heavy as iron came from balloon flights of cloud chambers and photographic emulsions [Freier et al, 1948a[Freier et al, , 1948b. Evidence of electrons in cosmic rays came from balloon flights of a cloud chamber [Earl, 1961] and a scintillator telescope [Meyer and Vogt, 1961].…”
Section: What Are Cosmic Rays? Geomagnetism Helps Find the Answermentioning
confidence: 99%
“…grains. Freier et al (1948b) take the minimum acceptable track length to be 1.5 microns, while Bradt and Peters use four grains in a Theoretical Number Following Bradt and Peters (1948), a theoretical expression for the number n of delta-rays per centimeter will be obtained. The number dn of such rays with energies between W and W+dW has been given by Mott (1929) 2 -14.…”
Section: Slide Rulementioning
confidence: 99%
“…The observation in 1948 of tracks produced by highly ionizing penetrating particles in balloon-borne nuclear emulsions [1] demonstrated that galactic cosmic rays (GCRs) contain elements heavier than H and He. Historical accounts of this discovery are given in [2,3].…”
Section: Introductionmentioning
confidence: 99%